The Development of Smart Bin Segregator System for Pet Bottles and Tin Cans Using Arduino with Charging Station Powered by Solar Panel for Bestlink College of the Philippines: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Smart Bin Segregator System using Arduino Uno with a charging station powered by a Solar panel is used for the segregation of the two kinds of waste materials that can be recycled: plastic bottles and tin cans with 2 minute interval time of charging that applies technology and its current trend to solid waste management to help the community for proper waste segregation and that will also help them save energy. The methodology used in this study is the sprint method, which is a time-boxed iteration of continuous development. Within a sprint, the team must complete the planned amount of work and be ready for review. It has six phases: understand, define, sketch, decide, prototype, and validate. The online survey results Slovin’s formula has been used to calculate the sample size to achieve a certain confidence interval when sampling an assumed population of hundred (100) respondents. The system device comprises a capacitive proximity, ultrasonic sensor, DIY weight sensor, solar panel, lead-acid battery, an inverter, lead-acid battery, servo motor, and Arduino Uno, which controls the whole system operation.The researchers concluded that this smart bin segregator system for pet plastic bottles and tin cans using Arduino Uno with a charging station powered by solar panels for Bestlink College of the Philippines would greatly help the school community. A Smart bin is indeed usable, for it could help the institution with proper waste management. This project design also significantly impacts the users of tin cans, and they will be able to see how it works due to the acrylic glass design.
Keywords: Arduino Uno; Ultrasonic sensor; buzzer; capacitive proximity sensor; solar panel; lead-acid battery; servo motor; inverter